A Phenomenological Study of Turnover and Attrition of High School Principals in Title I Rural School Districts in South Georgia - Andrews, Brandon (My University, 2026)
Principal turnover is on the rise in U.S. public schools (Pannell & McBrayer, 2022). Furthermore, Grissom et al. (2021) illustrated how school principal turnover can negatively impact student achievement. Approximately 25% of principals leave their schools every year, with 50% of new principals quitting within their third year (Alenezi, 2020). This phenomenological study explored the factors that contribute to turnover and attrition rates of high school principals in South Georgia. The researcher used purposeful sampling to select participants who were current or past principals of a Title I rural school for 3 to 5 years. Burnout and resource scarcity are factors of turnover and attrition; thus, the theoretical framework was the Maslach Burnout Inventory (MBI) and the Conservation of Resource theory (Beausaert et al., 2016; Hobfoll et al., 2018; Maness, 2021; Maslach et al., 1997). The data collection methods included a demographic survey along with items from the MBI for Educators Survey (MBI-ES) and a virtual one-on-one interview (Maslach et al., 1997). Data analysis consisted of a three-iteration coding process: 1) research questions, 2) theories, and 3) components of theories. Key findings such as professional departure factors and educational occupation experience highlighted factors of turnover and attrition. Additionally, participants emphasized administrative support systems and resilience as factors of retention. The study’s findings yielded several implications for district leadership, principals, professional leadership organizations, parents, and community leaders. District leadership may consider ways in which to provide administrative support, while principals may seek healthy coping strategies to relieve stress and avoid burnout.
Keywords: Educational leadership; Dissertations, Academic; School principals; Labor turnover; High schools; Burn out (Psychology); School administrators